Percutaneous vertebroplasty for SAPHO syndrome with vertebral destruction: a case report and literature review - Cheng, Yuanpei; Feng, Hao; Mu, Junhan; Chen, Jialin; Wu, Han (Frontiers in Medicine, 2023)
Synovitis, acne, pustulosis, hyperostosis and osteitis (SAPHO) syndrome is a rare musculoskeletal disease characterized by dermatological and osteoarticular lesions. However, SAPHO syndrome is difficult to be diagnosed due to the rarity and complexity. Additionally, there is no standard treatment for SAPHO syndrome based on limited experience. Percutaneous vertebroplasty (PVP) has rarely been reported to treat SAPHO syndrome. We reported a 52-year-old female patient who had a sex-month history of back pain. Palmoplantar pustulosis appeared on the hands and feet. Vertebral destruction was observed on computed tomography (CT) scanning. Laboratory examination showed that erythrocyte sedimentation rate (ESR) and C-reactive protein were elevated. Finally, the patient was diagnosed with SAPHO syndrome and treated with PVP. After the surgery, the back pain was significantly relieved. In this literature review, we mainly discussed the treatment methods of SAPHO syndrome, and provided a potential treatment for SAPHO syndrome, especially with vertebral destruction, kyphosis, and even pathological fractures.